A study of magnitude and correlates of altered bone mineral density in type 2 diabetes mellitus patients of central rural India - Reema, Ningthoukhongjam; Jain, Jyoti; Singh, Thangjam Gautam; Banait, Shashank (International Journal of Advances in Medicine, 2020)
Background: Diabetes mellitus is fast becoming the epidemic of the 21st century. It is a metabolic disease that affects multiple organ system in the body including bone metabolism and bone mass. There is high prevalence of decreased bone mineral density (BMD) in type 2 diabetes mellitus (T2DM) patients leading to osteoporosis, osteopenia and fracture. The aim of the present study was to find the magnitude and correlates of altered BMD in T2DM patients of central rural India. Methods: This cross-sectional study was carried out at a tertiary care teaching hospital in central rural India from 2014 to 2016. It comprises of 200 T2DM patients with aged ≥35 years. Bone mineral density measurements were done by using peripheral dual energy X-ray absorptiometry (DEXA). Results: Mean age of study subjects was 56.13±11.12 years with 43.5% males and 56.5% females. Our study results showed the magnitude of decreased BMD was 82%. 53% of the study subjects were osteoporotic and 29% were osteopenic. Significant associations were detected between decreased BMD and old age, female gender, high body mass index, high fasting blood sugar, high HbA1c and low serum calcium on multivariate analysis. Conclusions: The prevalence of decreased BMD in patients with T2DM of central rural India is high, especially in females’ patients, obese patients, and uncontrolled diabetic patients. Awareness amongst the health care provider of this changes will directly affect the treatment decisions for patients, thereby preventing osteoporosis, osteopenia and mitigating potential fracture risk.